Proteoglycans and Glycosaminoglycans in Misfolded Proteins Formation in Alzheimer's Disease - Wang, Peipei; Ding, Kan (Protein and Peptide Letters, 2014)
Misfolded protein amyloid-beta protein (Aβ) and tau protein are two high hallmarks of Alzheimer’s disease (AD), representing significant targets in treating AD. Researches on mechanisms of the two proteins inducing neuron dysfunctions provide therapeutic strategies of AD, including inhibition of Aβ production and aggregation, acceleration of Aβ clearance as well as reduction of tau hyperphosphorylation. Proteoglycans (PGs) consist of a core protein and glycosaminoglycans (GAGs) chains, with enormous structural diversity due to variation in the core protein, the number of GAGs chains as well as extent and position of sulfation. Considerable evidences have indicated that PGs and GAGs play important roles in Aβ and tau processing. Numbers of GAGs and analogues have potential therapeutic function in AD. In this Review, we focus on the relationship of PGs and GAGs with misfolded proteins in AD and their potential therapeutic implications.
Keywords: proteoglycans